Dimensional analysis of a questionnaire about ethnic prejudice - Rebolloso Pacheco, Enrique; Fernández Ramírez, Baltasar; Pozo Muñoz, Carmen; Hernández Plaza, Sonia; Rebolloso Pacheco, José Ramón (Apuntes de Psicología, 2022)
The study analyzes the dimensions of a multiscale questionnaire about ethnic prejudice toward North-Africans in Almería (Spain). The aim was to show the basic components of a scale of traditional prejudice, reliable in our context and useful for future research. Reliability is analyzed through convergence of different groups of items using various multivariate analysis procedures. A high convergence will show the most consistent and reliable dimensions in the measurement of ethnic prejudice, The questionnaire is a combination of several scales: favourability in the stereotype, social distance, principles of equality and politics ofimplementation ofthese principles. Results support the traditional character of the expression of prejudice reflected inthe scales. Two dimensions appear from the analyses: principles of equality (which include the scales of principles and politics and some items of social distance) and confidence in the interpersonal relations with the North-African population (some items of the stereotype scale). We suggest that situations of some degree of intimacy (that could be related with a subtle expression of prejudice) and the politics of limited expulsion and police border control are evaluated by respondents independently of other questions: individuals apparently not prejudiced may show rejection in these items.